2018
DOI: 10.11610/isij.4105
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Foundation of State’s Information Security in Social Networking Services in Conditions of Hybrid War

Abstract: At the present stage of the development of information technologies, social networking services have become a leading means of mass communication with a significant impact on all spheres of public activity. Thanks to its popularity and communication benefits, social networking services are used by leading nations to achieve their own geopolitical goals. Through information operations in social networking services, one can spread manifestations of hostility on national, religious, or ethnic grounds, and thus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…In particular, it can lead to mass protests of citizens, the radicalization of the society based on religious, ethnic, national and political grounds. The examples of "Colorful Revolutions" in the CIS together with "The Arab Spring" in the Middle East and North Africa demonstrate that achieving a reduction in the level of radicalization of society using existing legal mechanisms is a very challenging task [14][15][16]. In most cases, such events led not only to civil protests but also to the overthrow of governments, their change, civil wars and armed conflicts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it can lead to mass protests of citizens, the radicalization of the society based on religious, ethnic, national and political grounds. The examples of "Colorful Revolutions" in the CIS together with "The Arab Spring" in the Middle East and North Africa demonstrate that achieving a reduction in the level of radicalization of society using existing legal mechanisms is a very challenging task [14][15][16]. In most cases, such events led not only to civil protests but also to the overthrow of governments, their change, civil wars and armed conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective way to counteract the chaos of society is the timely detection of information operations in SNSs, which are conducted by the opposing party. Methods of identifying and assessing threats to information security of the state should be applied in such cases [14].…”
Section: Introductionmentioning
confidence: 99%
“…Under current conditions, the advantage in the state's information space is gained due to the high speed of content distribution in SNS, which has a destructive information impact on actors, as well as the decentralized nature of the links between them. As a result, SNS are an effective and efficient online platform for conducting offensive actions in the national information space of the state [6][7][8][9][10][11][12][13][14]. Therefore, at the present stage of the development of information technologies and the formation of the information society, SNS has become a source of threats to the information security of the state.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of recent research and publications has shown that, at the present stage of technology development, the hybrid war is being run without the use of military capabilities and weapons in the classical sense [7,10,15,16]. Due to the use of SNS, information confrontation becomes latent, has no clear beginning and end, and, as a result, the cross-border interaction between actors in SNS, the borders of states become vague.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation